Early Maternal Deprivation Enhances Voluntary Alcohol Intake Induced by Exposure to Stressful Events Later in Life. (2nd March 2015) - Peñasco, Sara; Mela, Virginia; López-Moreno, Jose Antonio; Viveros, María-Paz; Marco, Eva M.
Abstract : In the present study, we aimed to assess the impact of early life stress, in the form of early maternal deprivation (MD, 24 h on postnatal day, pnd, 9), on voluntary alcohol intake in adolescent male and female Wistar rats. During adolescence, from pnd 28 to pnd 50, voluntary ethanol intake (20%, v/v) was investigated using the two-bottle free choice paradigm. To better understand the relationship between stress and alcohol consumption, voluntary alcohol intake was also evaluated following additional stressful events later in life, that is, a week of alcohol cessation and a week of alcohol cessation combined with exposure to restraint stress. Female animals consumed more alcohol than males only after a second episode of alcohol cessation combined with restraint stress. MD did not affect baseline voluntary alcohol intake but increased voluntary alcohol intake after stress exposure, indicating that MD may render animals more vulnerable to the effects of stress on alcohol intake. During adolescence, when animals had free access to alcohol, MD animals showed lower body weight gain but a higher growth rate than control animals. Moreover, the higher growth rate was accompanied by a decrease in food intake, suggesting an altered metabolic regulation in MD animals that may interact with alcohol intake.